Wage-Fixing (Routledge Revivals) - Meade, J. (Routledge, 2013)
This reissue, first published in 1982, is the first of two volumes on the causes and cure of Stagflation - the two-headed monster that combines mass unemployment with rapid inflation, which affected contemporary economies across the industrially developped world in the 1970s. Professor Meade outlines the nature of the problem, contrasting the Great Slump of the 1930s with the Great Stagflation of the 1970s and comparing the Orthodox Keynesian and Monetarist approaches with the New Keynesian strategy. Various proposals for the reform of wage-fixing institutions are discussed, including the limitation of trade-union bargaining powers, an official incomes policy, labour management and ownership in business, and tax or subsidy measures to discourage inflationary rises in wages and prices. The book will be essential reading for all concerned with both the theory and policy of contemporary macroeconomics, industrial relations, labour economics and labour law. It has been written so that the general argument in the main text is accessible to the general reader as well as of interest to the professional economist.